Incidence and clinical characteristics of myeloproliferative neoplasms displaying a PDGFRB rearrangement - Arefi, Maryam; García, Juan L.; Peñarrubia, María J.; Queizán, José A.; Hermosín, Lourdes; López-Corral, Lucía; Megido, Marta; Giraldo, Pilar; de las Heras, Natalia; Vanegas, Raúl J.; Gutiérrez, Norma C.; Hernández-Rivas, Jesús M. (European journal of haematology, 2012)
Objectives The myeloproliferative neoplasms displaying a PDGFRB rearrangement are rare diseases derived from a haematopoietic stem cell. The goals of the study were to assess the incidence of these disorders and to define the clinical and biological characteristics as well as the response to the imatinib therapy. Methods A total of 556 patients with myeloproliferative neoplasms were studied by means of molecular cytogenetics. Results The incidence of myeloproliferative neoplasms (MPN) with PDGFRB rearrangement was low (10 cases, 1.8% of all MPN). Most of the patients showed moderate anaemia (median Hb was 10.0 gr/dL; range from 7.5 to 13 g/dL), leukocytosis (median white blood cells was 21.7 × 109/L with a range from 4 to 43 × 109/L) and eosinophilia (median circulating eosinophils was 2.4 × 109/L with a range of 1.1–5.7 × 109/L) with a median of bone marrow infiltration cells displaying PDGFRB rearrangement of 55% (range, 37–85%). In three cases, a t(5;12) was observed while two patients showed rearrangements of 17q21 region. In two cases, a del(5)(q31) was observed. Most of the patients responded to standard dosage of imatinib, and the response was maintained in the time in those patients with a follow‐up higher than 9 years. Conclusions The incidence of patients with PDGFRB rearrangement is low. These patients showed leukocytosis with eosinophilia and anaemia. The efficacy of imatinib therapy in patients showing PDGFRB rearrangement is high. For this reason, in all patients with MPN without any other molecular aberration, PDGFRB rearrangement should be ascertained.